Tổng hợp và chuyển hóa một số dẫn xuất 3-axetylcumarin - Thảo, Nguyễn Minh; Dũng, Đỗ Tiến; Vinh, Nguyễn Văn; Hà, Nguyễn Thu; Thuấn, Nguyễn Văn; Hường, Trần Thu (Vietnam Journal of Chemistry, 2014)
By the reaction of o-acylphenols with ethyl acetoacetate a new series of 3-acetylcoumarine derivatives were obtained. Some α,β-unsaturated ketones were also synthesized via 3-acetylcoumarine derivatives by Claisen-Schmidt condensed reaction. Ketones formed via 3-acetyl-4-methylcoumarine derivatives have interesting structures. The structures of these compounds were confirmed by IR, 1H-NMR and MS spectroscopic data